A History of Accounting in America: An Historical Interpretation of the Cultural Significance of Accounting (Book). - Burns, Thomas J.; Homburger, Richard H. (The Accounting Review, 1980)
Abstract Reviews the book "A History of Accounting in America: An Historical Interpretation of the Cultural Significance of Accounting," by Gary John Previtis and Barbara Dubis Merino.